1999
DOI: 10.1159/000027414
|View full text |Cite
|
Sign up to set email alerts
|

Leber’s Hereditary Optic Neuropathy Mitochondrial DNA Mutations at Nucleotides 11778 and 3460 in Multiple Sclerosis

Abstract: Objectives: Leber’s hereditary optic neuropathy (LHON) can be difficult to distinguish from optic neuritis seen in multiple sclerosis (MS). About half of the LHON patients harbor a mutation at nucleotide (nt) 11778 in the mitochondrial (mt) DNA. In addition, mutations at nt-3460 and nt-14484 have been associated with LHON. An association of LHON and MS has been suspected for decades, and, recently, the LHON nt-11778 and nt-3460 mtDNA mutations have been found in several patients with MS or MS-like disease. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…Since Harding et al [2]reported on 8 LHON women with the nucleotide (nt) 11778 mutation and multiple sclerosis (MS), many further reports have verified the relationship of LHON and MS [3, 4, 5, 6, 7, 8, 9]. The association of LHON and MS has been reported to be more than a coincidence, and that carrying a primary LHON mutation is a risk factor for developing MS, at least in Caucasian populations [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since Harding et al [2]reported on 8 LHON women with the nucleotide (nt) 11778 mutation and multiple sclerosis (MS), many further reports have verified the relationship of LHON and MS [3, 4, 5, 6, 7, 8, 9]. The association of LHON and MS has been reported to be more than a coincidence, and that carrying a primary LHON mutation is a risk factor for developing MS, at least in Caucasian populations [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several other patients with primary LHON mutations and an MSlike disease have subsequently been reported [1,3,8,9,14,20,23,28,30,32,37,40,42]. A higher frequency of secondary mutations in MS has also been reported [5,17,18], but this finding is questioned since other reports show an equal distribution of the incidence of these secondary mutations in LHON, MS, and the normal population [20,45].…”
Section: Introductionmentioning
confidence: 99%
“…Vanopdenbosch et al [23]showed that the association of LHON and MS is more than a coincidence, and that carrying a primary LHON mutation is a risk factor for developing MS. Moreover, mitochondrial primary point mutations at np 11,778 or 3,460 have been detected in some individuals affected by MS with an early and severe optic nerve involvement [24, 25]. Meanwhile, the results of several studies suggest a multifactorial etiology for MS, including multiple genetic factors of moderate effect rather than a very few genes of major biologic importance [26].…”
Section: Discussionmentioning
confidence: 99%